Integrasi Pasar dan Keterkaitan Harga Karet Indonesia dengan Singapura - Pantjar Simatupang; Jefferson Situmorang (Pusat Sosial Ekonomi dan Kebijakan Pertanian, 1988)
EnglishIncreasing non-oil export earning is one of Indonesia economic development priority. Its traditional non-oil export commodities are agricultural products. One of the major agricultural commodities is rubber. For this, improvement international market is very crucial. The efficient international market is also important in increasing the rubber farmers income. This paper analyzes the Jakarta-Singapore rubber and their price interrelationships. The analysis is conducted using a system of vektor autoregresion price equations. This analytical tool is considered better than the convensional market integration analytical tools, such as correlations and simple regression. Therefore the analytical method used in this study is recommended. for other market integration researchers. This paper shows that the Jakarta and Singapore rubber markets are strongly integrated. That is, none of the market strong enough to take the price leader position. In other words, the two market are competitive. The price adjustment process in Singapore is, however, faster than in Jakarta. The Singapore market is more efficient. The price adjustment process is asymmetry. The marketing margin trends increasing if the price increases and decreasing if the price falls. This makes the price portion received by the rubber farmers from price increase lower than the portion received by exporters. Therefore, the government should increase competitions among the exporters, for example through further trade deregulation and increasing the number of exporters. The price information dissamination process should also be improved by increasing working efficiency and effectivity of the Market Information Board.IndonesianPeningkatan nilai ekspor non migas merupakan salah satu prioritas pembangunan ekonomi Indonesia dewasa ini. Ekspor non-migas tradisional utama Indonesia adalah ekspor hasil-hasil pertanian. Salah satu komoditas ekspor pertanian utama Indonesia adalah karet. Dalam usaha peningkatan ekspor karet tersebut dapat ditempuh dengan memperbaiki sistem pemasaran ekspor. Sistem pemasaran eksppr tersebut juga berpengaruh penting terhadap tingkat harga yang diterima oleh petani karet. Salah satu tujuan tulisan ini adalah membahas integrasi pasar dan mekanisme rambatan harga karet Jakarta dan Singapore. Metode analisis yang digunakan adalah sistem persamaan autoregion yang dipandang lebih baik dari metode korelasi dan regresi sederhana yang umum digunakan di Indonesia. Dengan demikian, metode autoregresi seperti yang ditempuh dalam tulisan ini dianjurkan untuk dipakai meneliti lainnya. Penelitian menunjukkan bahwa karet Jakarta dan Singapore terintegrasi kuat. Harga dibentuk bersama-sama. Tidak ada salah satu pasar yang begitu kuat dan mampu bertindak sebagai pembikin harga. Namun penguasaan harga di pasar Singapura lebih kuat daripada di pasar Jakarta. Pasar Singapura lebih efisien. Penyesuaian harga diantara kedua pasar tidak sebangun. Marjin pemasaran cenderung meningkat pada waktu harga naik dan menurun pada waktu harga turun. Hal ini menyebabkan bagian harga yang diterima petani lebih kecil dari yang diterima eksportir dari kenaikan harga. Pemerintah haruslah meningkatkan persaingan diantara eksportir melalui deregulasi, memperbanyak eksportir. Sistem informasi pasar perlu pula ditingkatkan dengan lebih mengefektifkan Lembaga Informasi Pasar.